The Efficacy and Safety of Continuous Intravenous Endostar Treatment Combined With Concurrent Chemoradiotherapy in Patients With Locally Advanced Cervical Squamous Cell Carcinoma: A Randomized Controlled Trial - Shu, Hang; Dong, Yaqin; Xu, Zhonghua; Luo, Weiwei; Xu, Lei; Zhu, Haochen; Cheng, Linghui; Lv, Yin (Frontiers in Oncology, 2021)
Objective: To investigate the short-term efficacy and safety of Endostar combined with concurrent chemoradiotherapy in the treatment of locally advanced cervical squamous cell carcinoma (LACSC). Methods: A total of 91 patients with LACSC admitted to the First Affiliated Hospital of Anhui Medical University from June 2019 to December 2020 were randomly assigned to either the experimental group (n = 48) or control group (n = 43). The control group received radiotherapy for cervical cancer and paclitaxel combined with platinum chemotherapy (CCRT), and the experimental group received Endostar continuous intravenous infusion of anti-angiogenic therapy plus CCRT. The short-term efficacy, common clinical indicators, tumor indicators, changes in serum vascular endothelial growth factor-A (VEGF-A), and the occurrence of adverse events (AEs) were explored after treatment. Results Compared with the control group, the complete response (CR) rate in the experimental group was significantly increased (83.33% vs 65.12%, P < 0.05). Both routine indicators and tumor indicators in the two groups were significantly decreased compared to before treatment. Compared with the control group, patients in the experimental group had higher incidences of neutropenia, hypertension, and infection, but lower incidence of nausea. After treatment, the serological expression of VEGF-A was significantly decreased in both groups. Conclusion: Endostar combined with CCRT in the treatment of LACSC can further improve the efficacy of CR rate and significantly reduce serum tumor indicators and VEGF-A levels, with mild and controllable AEs. Endostar combined with CCRT is expected to be a new treatment regimen for LACSC.